Anemia during treatment with peginterferon Alfa‐2b/ribavirin and boceprevir: Analysis from the serine protease inhibitor therapy 2 (SPRINT‐2) trial1234. Issue 3 (11th February 2013) - Sulkowski, Mark S.; Poordad, Fred; Manns, Michael P.; Bronowicki, Jean‐Pierre; Rajender Reddy, K.; Harrison, Stephen A.; Afdhal, Nezam H.; Sings, Heather L.; Pedicone, Lisa D.; Koury, Kenneth J.; Sniukiene, Vilma; Burroughs, Margaret H.; et al.
Abstract Boceprevir (BOC) added to peginterferon alfa‐2b (PegIFN) and ribavirin (RBV) significantly increases sustained virologic response (SVR) rates over PegIFN/RBV alone in previously untreated adults with chronic hepatitis C genotype 1. We evaluate the relationship of incident anemia with triple therapy. A total of 1, 097 patients received a 4‐week lead‐in of PegIFN/RBV followed by: (1) placebo plus PegIFN/RBV for 44 weeks (PR48); (2) BOC plus PegIFN/RBV using response‐guided therapy (BOC/RGT); and (3) BOC plus PegIFN/RBV for 44 weeks (BOC/PR48). The management of anemia (hemoglobin [Hb] <10 g/dL) included RBV dose reduction and/or erythropoietin (EPO) use. A total of 1, 080 patients had ≥1 Hb measurement during treatment. The incidence of anemia was 50% in the BOC arms combined (363/726) and 31% in the PR48 arm (108/354, P < 0.001). Among BOC recipients, lower baseline Hb and creatinine clearance were associated with incident anemia. In the BOC‐containing arms, anemia was managed by the site investigators as follows: EPO without RBV dose reduction, 38%; RBV dose reduction without EPO, 8%; EPO with RBV dose reduction, 40%; and neither RBV dose reduction nor EPO, 14%. SVR rates were not significantly affected by management strategy (70%‐74%), and overall patients with anemia had higher rates of SVR than those who did not develop anemia (58%). Serious and life‐threatening adverse events (AEs) and discontinuations due to AEs among BOC‐treated patients did not differ by EPO use. Conclusion: With BOC/PR therapy, SVR rates in patients with incident anemia were higher than nonanemic patients and did not vary significantly according to the investigator‐selected approach for anemia management. Prospective studies are needed to confirm this observation. (HEPATOLOGY 2013)